EVALUASI METODOLOGI WATERFALL DAN AGILE: STUDI LITERATUR PADA SISTEM PERPUSTAKAAN - Maulana, Muhammad Reza (Universitas Lampung, 2025)
School libraries play a crucial role in supporting educational activities by providing adequate learning resources. However, manual management practices often hinder operational efficiency, as observed in SDK Buntal, Manggarai Timur, and SD Muhammadiyah 10 Palembang. To address these challenges, this study evaluates the implementation of website-based library systems using Waterfall and Agile methodologies. The research employs a library research approach, gathering data from relevant literature, and utilizes descriptive methods to analyze the characteristics and effectiveness of each methodology. Results indicate that the Waterfall approach offers a clear and structured development process, suitable for stable requirements, while Agile provides flexibility and adaptability, allowing iterative improvements based on user feedback. This comparative analysis highlights the strengths and limitations of both methodologies in enhancing library management. The findings serve as a practical guide for educational institutions in selecting the appropriate methodology to optimize library operations. This research contributes to the broader understanding of software development strategies in education-focused systems.